The Mathematics Education Traditions of Europe (METE) Project - Török, Judit (Teaching Mathematics and Computer Science, 2006)
This study is based on the work of the METE (Mathematics Education Traditions of Europe Project) team. Following a short introduction of the project, its theoretical background, methods and research design are presented in the next three sections. In the 4th section the tools developed by the METE team for qualitative and quantitative analysis of the collected data are discussed in details. The 5th section contains some personal remarks about using these tools. The 6th section presents the main results of the project, followed by a summary of the project's educational and theoretical significance.